Intensification of gas production from fields with unstable reservoirs - Kondrat, R. M.; Кondrat O. R.; Dremlyukh, N. S.; Ugrynovsky, A. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
The negative consequences of sand removal from the reservoir and methods of preventing the formation of sand plugs at the bottom of wells are indicated. According to the results of research on the well model, the minimum required gas velocities have been experimentally determined for the removal of sand particles of three different fractions. The optimal concentrations of foaming surface active substances (surfactants) and stabilizers in aqueous solutions have been chosen in order to obtain stable foam for sand plugs flushing on the wells. There has been experimentally set the velocity of the foam with the addition and without the addition of a foam stabilizer for the transfer of solid particles from the well. Two compositions of foaming surfactants and stabilizers have been developed, one of which is proposed for sand plugs flushing at the bottom of the well, and the other – for dosed injection into the annulus of the well to prevent accumulation of the solid phase at the bottom. Theoretical studies have substantiated the choice of the well bore diameter in the gas-bearing formation zone depending on the well productivity and determined the optimal values of the thickness and permeability of the gravel pack in the bottom hole zone of the well with unstable reservoirs, which prevent sand from passing the formation to the well. Theoretical studies have substantiated a rational correlation of diameters of tubing, columns of flexible pipes and the flow rate of the flushing agent for washing the sand plug in the wells with various flushing agents. The composition of the slurry solution has been chosen to create a cement stone with high values of strength and permeability in the bottomhole formation zone. To increase the efficiency and reduce the time and costs there has been proposed a device for the destruction of sand plugs, which consists of a housing with a check valve. A patent-protected design of the device for repairing the lower part of the production casing, damaged as a result of erosion destruction by particles of formation sand, has been proposed. An improved technology for improving the productivity of gas wells with unstable reservoirs has been offered.